Effect of ultrasonic pretreatment on melon drying and computational fluid dynamic modelling of thermal profile - Silva, João Henrique Fernandes da (Array, 2021)
Research background. Drying is one of the most traditional processes of food preservation. Optimizing the process can result in a competitive product on the market regarding its price and quality. A common method in use as a pretreatment to drying is ultrasound. The goal of this work is to analyze different drying methods with and without applying ultrasound (US) pretreatment on heat and mass transfer, simulating numerically the temperature profile by computational fluid dynamics (CFD). Experimental approach. The melon slices were pretreated with ultrasound for 10 (US10), 20 (US20) and 30 (US30) min at 25 kHz, and the water loss and solid gain were evaluated. Samples were dried at different temperatures (50, 60 and 70 °C). The effective diffusivity was estimated, and experimental data were modelled using empirical models. The airflow in the dryer and the temperature profile in the melon slice were simulated via computational fluid dynamics (CFD). Results and conclusions. Ultrasound pretreatment reduced the drying time from 25 % (samples US20 and US30 at 50 °C) to 40 % (samples US20 and US30 at 70 °C). The two-term exponential model presented the best fit to the experimental data, and the diffusivity coefficients showed a tendency to increase as the time of exposure of the melon to ultrasonic waves increased. Pretreatment water loss and solid gain behaviour and drying kinetic and diffusion data were used to choose the best experimental conditions to be simulated with CFD. The heat transfer modelling through CFD showed that the temperature distribution along the melon slice was representative. Therefore, the profile obtained via CFD satisfactorily describes the drying process. Novelty and scientific contribution. The use of simulation tools in real processes allows the monitoring and improvement of existing technologies, such as food drying processes, that involve complex mechanisms, making it difficult to obtain some data.